Evaluation of the Xpert HCV Viral Load point-of-care assay from venepuncture-collected and finger-stick capillary whole-blood samples: a cohort study. (July 2017) - Grebely, Jason; Lamoury, Francois M J; Hajarizadeh, Behzad; Mowat, Yasmin; Marshall, Alison D; Bajis, Sahar; Marks, Philippa; Amin, Janaki; Smith, Julie; Edwards, Michael; Gorton, Carla; Ezard, Nadine; et al.
Summary: Background: Point-of-care hepatitis C virus (HCV) RNA testing offers an advantage over antibody testing (which only indicates previous exposure), enabling diagnosis of active infection in a single visit. In this study, we evaluated the performance of the Xpert HCV Viral Load assay with venepuncture and finger-stick capillary whole-blood samples. Methods: Plasma and finger-stick capillary whole-blood samples were collected from participants in an observational cohort enrolled at five sites in Australia (three drug and alcohol clinics, one homelessness service, and one needle and syringe programme). We compared the sensitivity and specificity of the Xpert HCV Viral Load test for HCV RNA detection by venepuncture and finger-stick collection with the Abbott RealTime HCV Viral Load assay (gold standard). Findings: Of 210 participants enrolled between Feb 8, 2016, and July 27, 2016, 150 participants had viral load testing results for the three assays tested. HCV RNA was detected in 45 (30% [95% CI 23–38]) of 150 participants based on Abbott RealTime. Sensitivity of the Xpert HCV Viral Load assay for HCV RNA detection in plasma collected by venepuncture was 100·0% (95% CI 92·0–100·0) and specificity was 99·1% (95% CI 94·9–100·0). Sensitivity of the Xpert HCV Viral Load assay for HCV RNA detection in samples collected by finger-stick was 95·5% (95% CI 84·5–99·4) and specificity was 98·1% (95% CI 93·4–99·8). No adverse events caused by the index test or the reference standard were observed. Implications: The Xpert HCV Viral Load test can detect active infection from a finger-stick sample, which represents an advance over antibody-based tests that only indicate past or previous exposure. Funding: National Health and Medical Research Council (Australia), Cepheid, South Eastern Sydney Local Health District (Australia), and Merck Sharp & Dohme (Australia).